Shamba Shape Up Season 15 – Episode 22: Weather Episode (English) - Grossi, Amanda; Gamoyo, Majambo Jarumani; Ghosh, Aniruddha; Murega, Brendah; Njoroge, Ezekiel; Musilu, Bahati; Masika, Peter Silla; Murage, Paul; Muriuki, Edward (2025)
This special episode of Shamba Shape Up, titled "From Data to Delivery," provides a comprehensive look at Kenya's climate services ecosystem, tracing the complete journey of climate information from national data collection to last-mile delivery. Viewers go behind the scenes at the Kenya Meteorological Department (KMD) to see weather instruments collecting real-time data, meet forecasters interpreting global and local signals, and learn how seasonal outlooks are produced. The episode demonstrates how national forecasts flow through county-level systems strengthened by AICCRA, including the AgData Hub for improved data access and Participatory Scenario Planning (PSP) processes that bring together meteorologists, agricultural officers, livestock experts, extension staff, farmer representatives, NGOs, and private actors to co-produce tailored advisories. The program showcases how county extension teams translate seasonal forecasts into location-specific guidance on crops, livestock, water management, and risks. Finally, the episode highlights iShamba, the digital advisory platform with over 540,000 subscribed users, demonstrating how climate information reaches farmers directly through SMS, WhatsApp, and call-center interactions. By revealing the full chain from satellite data interpretation to farmer advisory delivery, the episode builds trust in climate services and shows how collaborative, people-driven systems empower smallholder farmers to make informed, climate-smart decisions.